2012
DOI: 10.1038/jhg.2012.9
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies SNP in DCC is associated with gallbladder cancer in the Japanese population

Abstract: Gallbladder cancer (GC) is a relatively uncommon cancer with higher incidence in certain areas including Japan. Because of the difficulty in diagnosis, prognosis of GC is very poor. To identify genetic determinants of GC, we conducted a genome-wide association study (GWAS) in 41 GC patients and 866 controls. Association between each single-nucleotide polymorphism (SNP) with GC susceptibility was evaluated by multivariate logistic regression analysis conditioned on age and gender of subjects. SNPs that showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Of the six EC susceptibility loci, we identified and found that only the minor allele of rs10953615 was a similar risk factor for gallbladder and esophageal carcinoma and this allele was associated with increased risk for both cancers [21]. The other five SNPs showed results that were inconsistent with previous studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Of the six EC susceptibility loci, we identified and found that only the minor allele of rs10953615 was a similar risk factor for gallbladder and esophageal carcinoma and this allele was associated with increased risk for both cancers [21]. The other five SNPs showed results that were inconsistent with previous studies.…”
Section: Discussionmentioning
confidence: 93%
“…Twenty SNPs (rs6736997, rs401681, rs6879627, rs9502893, rs9363918, rs4269383, rs3016539, rs7832232, rs10088262, rs10788473, rs12413624, rs10500715, rs1000589, rs1585440, rs9573163, rs9543325, rs4924935, rs225190, rs372883, and rs1547374) were selected from previous research of pancreatic cancer [15][16][17][18][19][20]. Four SNPs (rs975334, rs10953615, rs13294589, and rs7504990) were selected from previous research of gallbladder cancer [21]. All of the SNPs in this study had minor allele frequencies (MAFs) of >5 % in the Asian Population HapMap and had previously been reported to be associated with gastrointestinal cancer.…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…As mentioned above, according to our knowledge, only a single, small GWAS has been performed in patients with this tumor yet [68]. Although GWAS analyses can identify only common variants (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, genome-wide association analyses and functional studies have identified the p. D19H variant of the hepatic cholesterol hemitransporter (ABCG8) associated with susceptibility for human gallstones [55,66,67]. To our knowledge the only genome-wide association study (GWAS) of patients with gallbladder cancer published to date (https://www.ebi.ac.uk/gwas/) was conducted in a relatively small Japanese discovery cohort of 41 GC patients and 866 controls, and a subsequent validation cohort of 30 cases and 898 controls [68]. A strong positive signal (combined P = 7.46 × 10 -8 OR=6.95; 95% CI=3.43-14.08) was detected for rs7504990 within the DCC gene (deleted in colorectal cancer) on chromosome 18q21.3.…”
Section: Potential Susceptibility Genes For Gallbladder Cancermentioning
confidence: 99%
“…Using candidate gene association studies, we have previously identified several genetic variants in cholesterol metabolism, inflammation, hormonal and DNA-repair pathway as playing a significant role in vulnerability to GBC Srivastava et al, 2010Srivastava et al, , 2011aSrivastava et al, ,b, 2012. Recently, a genome-wide association study (GWAS) showed a significant association between DCC gene polymorphisms and GBC susceptibility in a Japanese population sample (Cha et al, 2012). However, the sample size of the study was very low and the study lacked independent replication.…”
Section: Introductionmentioning
confidence: 97%